Exploring Sustainable Strategies for Education through the Adoption of Digital Circular Economy Principles - Meria, Lista; Bangun, Cicilia Sriliasta; Edwards, John (Pandawan Sejahtera Indonesia, 2024)
This study investigates sustainable strategies in education by examining the adoption of digital circular economy principles, aiming to address the growing need for resource efficiency within educational systems. As educational institutions face pressures to reduce environmental impact and enhance sustainability, integrating circular economy practices offers promising pathways. The objective of this research is to explore how digital tools and circular principles can be effectively applied to minimize waste and promote resource regeneration in academic settings. A mixed-method approach was employed, combining qualitative case studies and quantitative surveys across several institutions actively implementing circular economy initiatives. Data was collected from educators, administrators, and students to assess the impact of digital circular models on resource management, cost-efficiency, and environmental awareness. Findings indicate that digital circular economy strategies, including digital resource sharing platforms and waste reduction initiatives, significantly enhance both operational sustainability and educational outcomes by fostering a culture of environmental responsibility. Furthermore, the adoption of these strategies has led to measurable reductions in material waste and increased awareness of sustainable practices among students and staff. The research concludes that digital circular economy principles are not only viable but also essential for creating a sustainable educational environment that aligns with global sustainability goals. These findings provide valuable insights for policymakers, educators, and stakeholders in education seeking to develop sustainable frameworks and underline the importance of continued investment in digital circular economy initiatives to support long-term educational and environmental objectives.